Resin composition
By grafting maleic anhydride in styrene-type elastomers to improve their grafting rate, combining thermosetting resins and curing accelerators, the problem of insufficient compatibility between modified styrene-type elastomers and thermosetting resins is solved, and better compatibility and performance improvements are achieved.
Patent Information
- Application Number
- CN202380087104.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-22
- Filing Date
- 2023-12-18
- Publication Date
- 2025-07-25
AI Technical Summary
The compatibility between commercially available acid-modified styrene-based elastomers and other components such as thermosetting resins is insufficient and needs to be improved.
A modified styrene-based elastomer with a grafting rate of maleic anhydride of 1.5 mass% or more was combined with a thermosetting resin, a curing accelerator was added, and the reaction was carried out under mild conditions to improve the compatibility.
The compatibility between the modified styrene-based elastomer and the thermosetting resin is improved, and the heat resistance and strength of the resin composition are enhanced.
Smart Images

Figure BDA0005455254940000111 
Figure BDA0005455254940000112 
Figure BDA0005455254940000121
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition. Background Art
[0002] Styrenic elastomers composed of copolymers of aromatic vinyl compounds and conjugated diene compounds, hydrogenated products thereof, etc. are used for various purposes. In order to impart properties such as adhesiveness and affinity, it is known to acid-modify styrenic elastomers with maleic anhydride (for example, refer to Patent Document 1, etc.).
[0003] Prior Art Documents
[0004] Patent Documents
[0005] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2013 - 028761 Summary of the Invention
[0006] Technical Problem to be Solved by the Invention
[0007] Acid-modified styrenic elastomers are usually produced by kneading styrenic elastomers with maleic anhydride. The compatibility of commercially available acid-modified styrenic elastomers with other components such as thermosetting resins is not sufficient, and thus it is necessary to improve the compatibility. Therefore, an object of the present invention is to provide a resin composition containing a modified styrenic elastomer having excellent compatibility with other components.
[0008] Means for Solving the Technical Problem
[0009] One aspect of the present invention relates to a resin composition as follows.
[0010] [1] A resin composition containing a modified styrenic elastomer having a grafting rate of maleic anhydride of 1.5 mass% or more and a thermosetting resin.
[0011] [2] The resin composition according to the above [1], wherein
[0012] the grafting rate is 1.5 to 10.0 mass%.
[0013] [3] The resin composition according to the above [1], wherein
[0014] the grafting rate is 1.8 to 10.0 mass%.
[0015] [4] The resin composition according to any one of the above [1] to [3], wherein
[0016] The thermosetting resin contains at least one selected from the group consisting of an epoxy resin, a cyanate resin, an acrylic resin, a silicone resin, a phenolic resin, a maleimide resin, a thermosetting polyimide resin, a polyurethane resin, a melamine resin, and a urea-formaldehyde resin.
[0017] [5] The resin composition according to any one of [1] to [4] above further contains a curing accelerator.
[0018] [6] The resin composition according to any one of [1] to [5] above, wherein
[0019] The content of the thermosetting resin is 10 parts by mass or more with respect to 100 parts by mass of the total amount of the modified styrene-based elastomer and the thermosetting resin.
[0020] Advantages of the Invention
[0021] According to the present invention, a resin composition containing a modified styrene-based elastomer having excellent compatibility with other components can be provided. Detailed Description of Embodiments
[0022] Hereinafter, preferred embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments. In this specification, the term "process" includes not only independent processes but also those that are included in this term even when they cannot be clearly distinguished from other processes as long as they achieve the intended function of the process. In this specification, regarding the term "layer", when observed in a plan view, it includes not only a structure formed over the entire surface but also a structure formed in a part.
[0023] In this specification, the numerical range represented by "~" means a range including the numerical values described before and after "~" as the minimum value and the maximum value, respectively. In the numerical ranges described stepwise in this specification, the upper limit value or the lower limit value of any stepwise numerical range can be replaced with the upper limit value or the lower limit value of another stepwise numerical range. Also, in the numerical ranges described in this specification, the upper limit value or the lower limit value of the numerical range can be replaced with the value shown in the examples. In this specification, when referring to the amounts of the respective components in the composition and when there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the plurality of substances present in the composition. "A or B" includes either A or B, and may also include both. "Solid content" means the non-volatile components in the resin composition other than the volatile substances (water, solvent, etc.). That is, the "solid content" means the components other than the solvent that do not volatilize and remain after drying the resin composition described below, and also includes components that are liquid, molasses-like, or wax-like at room temperature (25°C).
[0024] In this specification, "Compound A and Compound B are compatible" means that in a molded body obtained by mixing and molding Compound A and Compound B, a single glass transition temperature (Tg) that does not originate from either Compound A or Compound B is observed. Further, "Compound A and Compound B are incompatible" means that in a molded body obtained by mixing Compound A and Compound B, only the Tgs originating from Compound A and Compound B, respectively, are observed.
[0025] In this specification, a "domain" means one phase constituting a phase-separated structure. In the case where a molded body obtained by mixing different polymers has a phase-separated structure, the Tgs originating from each domain are observed. When the Tgs originating from different domains are close, even if they are incompatible, it may sometimes be observed as if representing a single Tg, and thus it is necessary to verify by changing the mixing ratio or the like.
[0026] As a method for evaluating the compatibility of a polymer blend, there is a method of measuring the domain size of microphase separation present when observing the cross-section of a film molded body. The cross-section of the film molded body can be observed by using an atomic force microscope (AFM), a scanning electron microscope (SEM), a transmission electron microscope (TEM), or the like.
[0027] [Resin composition]
[0028] The resin composition according to this embodiment contains a modified styrenic elastomer having a graft ratio of maleic anhydride of 1.5 mass% or more and a thermosetting resin. The modified styrenic elastomer according to this embodiment has reactivity with the thermosetting resin, and the cured product of this resin composition is excellent in heat resistance, strength, and the like.
[0029] The resin composition according to this embodiment can be produced by mixing a modified styrenic elastomer and a thermosetting resin. The resin composition may further contain other components such as a curing accelerator, a filler, and a flame retardant.
[0030] (Modified styrenic elastomer)
[0031] The modified styrenic elastomer according to this embodiment has a graft ratio of maleic anhydride of 1.5 mass% or more. By increasing the graft ratio of maleic anhydride in the modified styrenic elastomer, the compatibility with other components (especially the thermosetting resin) can be improved.
[0032] The modified styrenic elastomer according to this embodiment can be produced by reacting maleic anhydride with a styrenic elastomer and has a succinic anhydride group based on maleic anhydride in the side chain. The styrenic elastomer may be a copolymer having a structural unit derived from a styrenic compound and a structural unit derived from a conjugated diene compound.
[0033] As styrene compounds, for example, styrene, d-methylstyrene, p-methylstyrene, and p-tert-butylstyrene can be cited. Among them, from the viewpoints of availability and productivity, styrene, α-methylstyrene, and 4-methylstyrene are preferred, and styrene is more preferred.
[0034] As conjugated diene compounds, for example, 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 1,3-pentadiene (piperylene), 1-phenyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-methyl-1,3-pentadiene, 3,4-dimethyl-1,3-hexadiene, and 4,5-diethyl-1,3-octadiene can be cited. Among them, from the viewpoints of availability and productivity, 1,3-butadiene and isoprene are preferred.
[0035] The styrenic elastomer may be a hydrogenated styrenic elastomer in which at least a part of the structural unit derived from the conjugated diene compound is hydrogenated. As the hydrogenated styrenic elastomer, for example, a hydrogenated product of a styrene-butadiene-styrene block copolymer (SEBS) and a hydrogenated product of a styrene-isoprene-styrene block copolymer can be cited. As commercially available products of SEBS, for example, the Tuftec (registered trademark) H series manufactured by ASAHI KASEI CORPORATION, the SEPTON (registered trademark) series manufactured by KURARAY CO., LTD., the KRATON (registered trademark) G polymer series manufactured by KRATON CORPORATION, etc. can be cited.
[0036] From the viewpoint of further improving compatibility, the acid value of the modified styrenic elastomer may be 20 to 120 mgKOH / g, 25 to 100 mgKOH / g, 30 to 90 mgKOH / g, or 35 to 80 mgKOH / g.
[0037] From the viewpoint of further improving compatibility, the grafting rate of maleic anhydride in the modified styrenic elastomer may be 1.5% by mass or more, 1.8% by mass or more, 2.0% by mass or more, 2.5% by mass or more, or 3.0% by mass or more. From the viewpoint of improving dielectric properties, the grafting rate of maleic anhydride may be 10.0% by mass or less, 9.0% by mass or less, 8.0% by mass or less, or 7.0% by mass or less. The above grafting rate may be 1.5 to 10.0% by mass, 1.8 to 10.0% by mass, 2.0 to 9.0% by mass, 2.5 to 8.0% by mass, or 3.0 to 7.0% by mass. Regarding the grafting rate, it can be calculated using the acid value of the modified styrenic elastomer. In addition, the acid value and grafting rate in this specification are values calculated by the methods described in the examples.
[0038] The manufacturing method of the modified styrene-based elastomer according to this embodiment includes a step of adding a radical initiator to a mixed solution obtained by dissolving a styrene-based elastomer and maleic anhydride in a solvent under a nitrogen atmosphere, and reacting maleic anhydride with the styrene-based elastomer.
[0039] The reaction temperature can be 60 - 100 °C, 65 - 95 °C, or 70 - 90 °C. Thus, compared with the conventional method of melt-kneading a styrene-based elastomer and maleic anhydride at a high temperature of 170 °C or higher to react maleic anhydride with the styrene-based elastomer, the modified styrene-based elastomer can be obtained under mild conditions, and the grafting rate of maleic anhydride can be increased. From the viewpoint of suppressing side reactions, unreacted maleic anhydride can be removed by extraction after the reaction.
[0040] From the viewpoint of further increasing the grafting rate, the blending amount of maleic anhydride can be 5 parts by mass or more, 8 parts by mass or more, 10 parts by mass or more, or 15 parts by mass or more relative to 100 parts by mass of the styrene-based elastomer. From the viewpoint of suppressing side reactions, the blending amount of maleic anhydride can be 50 parts by mass or less, 45 parts by mass or less, 40 parts by mass or less, or 35 parts by mass or less relative to 100 parts by mass of the styrene-based elastomer. The blending amount of maleic anhydride can be 5 - 50 parts by mass, 8 - 45 parts by mass, 10 - 40 parts by mass, or 15 - 35 parts by mass.
[0041] As the radical initiator, for example, organic peroxides, azo compounds, etc. can be used. As the organic peroxides, for example, dicumyl peroxide, benzoyl peroxide, 2-butanone peroxide, tert-butyl peroxybenzoate, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, bis(tert-butylperoxyisopropyl)benzene, and tert-butyl hydroperoxide can be cited. As the azo compounds, for example, 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-methylbutyronitrile), and 1,1'-azobis(cyclohexanecarbonitrile) can be cited.
[0042] As the solvent, for example, butyl cellosolve, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, toluene, xylene, mesitylene, ethyl methoxyacetate, ethyl ethoxyacetate, ethyl butoxyacetate, and ethyl acetate can be cited. They can be used alone or in combination of two or more. Among them, from the viewpoint of solubility, toluene, xylene, and propylene glycol monomethyl ether are preferred.
[0043] (Thermosetting resin)
[0044] As thermosetting resins, for example, epoxy resins, cyanate ester resins, acrylic resins, silicone resins, phenolic resins, maleimide resins, thermosetting polyimide resins, polyurethane resins, melamine resins, and urea-formaldehyde resins can be mentioned. They can be used alone or in combination of two or more.
[0045] As epoxy resins, for example, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, alicyclic epoxy resins, aliphatic chain epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, phenol aralkyl type epoxy resins, naphthol novolac type epoxy resins, naphthol aralkyl type epoxy resins, xylene-novolac type epoxy resins, bifunctional biphenyl type epoxy resins, biphenyl aralkyl type epoxy resins, dicyclopentadiene type epoxy resins, and dihydroanthracene type epoxy resins can be mentioned.
[0046] The content of the thermosetting resin in the resin composition is not particularly limited. Regarding the content of the thermosetting resin, for example, it can be 10 parts by mass or more, 20 parts by mass or more, 30 parts by mass or more, or 40 parts by mass or more, and can also be 95 parts by mass or less, 90 parts by mass or less, 85 parts by mass or less, or 80 parts by mass or less, based on 100 parts by mass of the total amount of the modified styrene-based elastomer and the thermosetting resin.
[0047] (Curing accelerator)
[0048] The resin composition according to the present embodiment may further contain a curing accelerator. As the curing accelerator, for example, various imidazole compounds which are latent thermal curing agents, BF3 amine complexes, phosphorus-based curing accelerators, etc. can be mentioned. In the case of formulating a curing accelerator, from the viewpoints of the storage stability of the resin composition, the workability of the semi-cured resin composition, and the solder heat resistance of the cured product, imidazole compounds and phosphorus-based curing accelerators are preferred.
[0049] (Filler)
[0050] The resin composition according to the present embodiment may further contain a filler. As the filler, for example, silica, alumina, titanium oxide, mica, beryllium oxide, barium titanate, potassium titanate, strontium titanate, calcium titanate, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, calcined clay, talc, aluminum borate, and silicon carbide can be mentioned. They can be used alone or in combination of two or more.
[0051] There are no particular restrictions on the shape and particle size of the filler. For example, the particle size of the filler can be 0.01 to 20 μm, or it can be 0.1 to 10 μm. Here, the particle size refers to the average particle size, which is the particle size at the point corresponding to 50% of the volume when obtaining the cumulative frequency distribution curve based on the particle size with the total volume of the particles being 100%. The average particle size can be measured using a particle size distribution measuring device employing the laser diffraction scattering method or the like.
[0052] For the purpose of improving the dispersibility of the filler, the adhesion to the organic component, etc., a coupling agent can be used in combination as needed. There is no particular limitation on the coupling agent. For example, various silane coupling agents, titanate coupling agents, etc. can be used. They can be used alone as one type, or two or more types can be used in combination. Also, the amount of the coupling agent used is not particularly limited. For example, it can be set to 0.1 to 5 parts by mass, or it can be set to 0.5 to 3 parts by mass relative to 100 parts by mass of the filler used. As long as it is within this range, the reduction of various properties is less, and it is easy to effectively exhibit the advantages brought by using the filler.
[0053] In the case of using a coupling agent, it can be the so-called integral blend treatment method of adding the coupling agent after blending the filler in the resin composition, but preferably the method of using a filler that has been subjected to dry or wet surface treatment with a coupling agent in advance. By using this method, the above-mentioned advantages of the filler can be more effectively exhibited.
[0054] (Flame retardant)
[0055] The resin composition according to this embodiment can further contain a flame retardant. There is no particular limitation on the flame retardant, and bromine-based flame retardants, phosphorus-based flame retardants, metal hydroxides, etc. are preferably used. As bromine-based flame retardants, for example, brominated epoxy resins, brominated additive flame retardants, brominated reactive flame retardants containing unsaturated double bond groups, etc. can be cited. As phosphorus-based flame retardants, for example, aromatic phosphates, phosphonates, hypophosphites, phosphazene compounds, etc. can be cited. As metal hydroxide flame retardants, for example, magnesium hydroxide, aluminum hydroxide, etc. can be cited.
[0056] As needed, the resin composition can be diluted with a solvent. There is no particular limitation on the solvent, and the volatility during film formation, etc. can be determined considering the boiling point. As the solvent, for example, solvents with relatively low boiling points such as methanol, ethanol, 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, methyl ethyl ketone, acetone, methyl isobutyl ketone, toluene, xylene, etc. can be cited. The solvent can be used alone as one type or in combination of two or more types.
[0057] The resin composition of the present embodiment can be obtained by uniformly dispersing and mixing the above-mentioned components, and there are no particular limitations on its preparation means, conditions, etc. For example, it can be mentioned that after sufficiently and uniformly stirring and mixing various components in a specified blending amount by a mixer or the like, kneading is performed using a mixing roll, an extruder, a kneader, a roll, an extruder, etc., and then the obtained kneaded product is cooled and pulverized. In addition, there are no particular limitations on the kneading form.
[0058] [Resin film]
[0059] A resin film can be made using the resin composition according to the present embodiment. In addition, a resin film refers to an uncured or semi-cured film-like resin composition.
[0060] There are no particular limitations on the method for producing a resin film. However, for example, it is obtained by drying a resin layer formed by coating a resin composition on a support substrate. Specifically, after coating the above resin composition on a support substrate using a kiss coater, a roll coater, a comma coater, etc., drying is performed in a heating drying furnace, etc., at a temperature of, for example, 70 to 250 °C, preferably 70 to 200 °C, for 1 to 30 minutes, preferably 3 to 15 minutes. Thereby, a resin film in a semi-cured state of the resin composition can be obtained.
[0061] The semi-cured resin film can be further heated in a heating furnace, for example, at a temperature of 170 to 250 °C, preferably 185 to 230 °C, for 60 to 150 minutes to thermally cure the resin film.
[0062] Regarding the thickness of the resin film according to the present embodiment, there are no particular limitations, but it is preferably 1 to 200 μm, more preferably 2 to 180 μm, and still more preferably 3 to 150 μm. By setting the thickness of the resin film within the above range, it is easy to balance the thinning of the printed wiring board obtained using the resin film according to the present embodiment and good high-frequency characteristics.
[0063] Regarding the support substrate, there are no particular limitations, but it is preferably at least one selected from the group consisting of glass, metal foil, and PET film. Since the resin film has a support substrate, its storage property and processability during the manufacture of a printed wiring board tend to be improved. That is, the resin film according to the present embodiment can be in the form of a support body with a resin layer including the resin composition according to the present embodiment and a support substrate, and can be peeled off from the support substrate during use.
[0064] [Prepreg]
[0065] A prepreg can be made using the resin composition according to this embodiment. The resin composition according to this embodiment can be coated on a fiber substrate as a reinforcing substrate, and the coated resin composition can be dried to obtain a prepreg. Also, a prepreg can be obtained by impregnating a fiber substrate with the resin composition according to this embodiment and then drying the impregnated resin composition. Specifically, the fiber substrate with the resin composition attached is heated and dried in a drying oven at a temperature of usually 80 to 200°C for 1 to 30 minutes to obtain a prepreg in which the resin composition is semi-cured. From the viewpoint of good formability, the amount of the resin composition attached to the fiber substrate is preferably coated or impregnated such that the resin content in the dried prepreg becomes 30 to 90% by mass.
[0066] There is no particular limitation on the reinforcing substrate of the prepreg, but a sheet-like fiber substrate is preferred. As the sheet-like fiber substrate, for example, inorganic fibers such as E glass, NE glass, S glass, and Q glass; organic fibers such as polyimide, polyester, and tetrafluoroethylene can be cited. As the sheet-like fiber substrate, substrates having shapes such as woven fabric, non-woven fabric, and chopped strand mat can be used.
[0067] [Laminated board]
[0068] According to this embodiment, a laminated board having a resin layer and a conductor layer including a cured product of the above resin composition can be provided. For example, a metal-clad laminate can be manufactured using the above resin film or the above prepreg.
[0069] The manufacturing method of the metal-clad laminate is not particularly limited. However, for example, by overlapping one or more layers of the resin film or prepreg according to this embodiment, and disposing a metal foil serving as a conductor layer on at least one surface, and for example, heating and pressing at a temperature of 170 to 250°C, preferably 185 to 230°C and a pressure of 0.5 to 5.0 MPa for 60 to 150 minutes, a metal-clad laminate having a metal foil on at least one surface of the resin layer or prepreg serving as an insulating layer is obtained. The heating and pressing can be carried out, for example, under a vacuum degree of 10 kPa or less, preferably 5 kPa or less. From the viewpoint of improving efficiency, it is preferably carried out in a vacuum. Regarding the heating and pressing, it is preferably carried out from 30 minutes after the start to the end of the forming.
[0070] [Multi-layer printed wiring board]
[0071] According to this embodiment, a multi-layer printed wiring board having a resin layer and a circuit layer including a cured product of the above resin composition can be provided. The upper limit value of the number of circuit layers is not particularly limited and can be 3 to 20 layers. The multi-layer printed wiring board can be manufactured, for example, using the above resin film, prepreg, or metal-clad laminate.
[0072] The manufacturing method of the multilayer printed wiring board is not particularly limited. However, for example, first, a resin film is disposed on one or both surfaces of a core substrate that has undergone circuit formation processing, or a resin film is disposed between a plurality of core substrates, and after performing pressure and heat lamination forming or pressure and thermocompression forming to bond the layers, laser drilling processing, drilling processing, metal plating processing, and circuit formation processing based on metal etching, etc. are performed, whereby a multilayer printed wiring board can be manufactured. When the resin film has a support substrate, the support substrate can be peeled off before disposing the resin film on the core substrate or between the core substrates, or the support substrate can be peeled off after attaching the resin layer to the core substrate.
[0073] As described above, the preferred embodiments of the present invention have been described, but these are examples for explaining the present invention, and the main purpose is not to limit the scope of the present invention only to these embodiments. The present invention can be implemented in various ways different from the above embodiments within the scope not departing from its main purpose.
[0074] Examples
[0075] Hereinafter, the present invention will be further described in detail based on examples. However, the present invention is not limited to the following examples.
[0076] [Modified styrene-based elastomer]
[0077] (Example 1)
[0078] In a 2 L flask equipped with a cooling tube, a nitrogen inlet tube, a thermocouple, and a stirrer, 950 g of xylene, 100 g of a hydrogenated styrene-based thermoplastic elastomer (manufactured by ASAHI KASEI CORPORATION, trade name “Tuftec H1041”), and 12.5 g of maleic anhydride (FUJIFILM Wako Pure Chemical Corporation) were added, and after stirring at 80 °C for 0.5 hour, nitrogen bubbling was performed at a flow rate of 0.5 cm 3 / L for 1.0 hour. Subsequently, 4.8 g of benzoyl peroxide (FUJIFILM Wako Pure Chemical Corporation) was added, nitrogen bubbling was performed at 80 °C, and stirring was carried out for 6.0 hours to effect a reaction. Unreacted maleic anhydride was extracted from the reaction solution three times with isopropanol and concentrated. The concentrate was vacuum dried at 70 °C to obtain a modified styrene-based elastomer (A1) having a succinic anhydride group.
[0079] (Example 2)
[0080] Except that the amount of maleic anhydride was changed to 17 g and the amount of benzoyl peroxide was changed to 6.5 g, the reaction was carried out in the same manner as in Example 1 to obtain a modified styrenic elastomer (A2) having succinic anhydride groups.
[0081] (Example 3)
[0082] Except that the amount of maleic anhydride was changed to 34 g and the amount of benzoyl peroxide was changed to 13 g, the reaction was carried out in the same manner as in Example 1 to obtain a modified styrenic elastomer (A3) having succinic anhydride groups.
[0083] (Example 4)
[0084] Except that the amount of maleic anhydride was changed to 8 g and the amount of benzoyl peroxide was changed to 3 g, the reaction was carried out in the same manner as in Example 1 to obtain a modified styrenic elastomer (A4) having succinic anhydride groups.
[0085] (Comparative Example 1)
[0086] Except that the amount of maleic anhydride was changed to 4 g and the amount of benzoyl peroxide was changed to 1.5 g, the reaction was carried out in the same manner as in Example 1 to obtain a modified styrenic elastomer (A5) having succinic anhydride groups.
[0087] (Comparative Example 2)
[0088] A modified styrenic elastomer (A6) (ASAHI KASEI CORPORATION, trade name “Tuftec M1913”) having commercially available succinic anhydride groups was prepared.
[0089] [Evaluation]
[0090] The acid value and the grafting rate of maleic anhydride of the modified styrenic elastomers of the examples and comparative examples were measured by the following steps. The results are shown in Table 1.
[0091] (Acid value)
[0092] 0.5 mL of distilled water was added to a liquid obtained by mixing about 1 g of the modified styrenic elastomer and 200 g of xylene at 80°C, and then, the mixture was stirred at the reflux temperature for 1 hour to hydrolyze the succinic anhydride groups. The mixture was cooled to 80°C, and after adding a small amount of phenolphthalein, an ethanol solution containing 0.1 M potassium hydroxide (KOH) was added dropwise for 30 seconds until the color did not disappear. The acid value (mgKOH / g) was measured based on the amount of the modified styrenic elastomer and the amount of KOH after dropping. The acid value of the modified styrenic elastomer is the value of two carboxyl groups generated from the hydrolysis of the succinic anhydride groups.
[0093] (Grafting ratio)
[0094] Regarding the grafting ratio of maleic anhydride to the modified styrene-based elastomer, it is calculated by substituting the acid value, the molecular weight of KOH, and the molecular weight of maleic anhydride into the following formula.
[0095] Grafting ratio (mass %) = [Acid value (mgKOH / g) / Molecular weight of KOH (mg / mol)] × 0.5 × Molecular weight of maleic anhydride (g / mol) × 100 (%)
[0096] [Table 1]
[0097]
[0098] (Compatibility)
[0099] As the thermosetting resin, thermosetting resin (B1) (xylene-novolac type epoxy resin, manufactured by Mitsubishi Chemical Corporation, trade name “YX7700”) and thermosetting resin (B2) (bismaleimide resin, manufactured by DIC Corporation, trade name “NE-X-9470S”) were prepared. As the unmodified styrene-based elastomer, “Tuftec H1041” was prepared. The modified styrene-based elastomer or unmodified styrene-based elastomer and the thermosetting resin were mixed at the mass ratios shown in Table 2 or Table 3 to prepare a resin composition. 0.05 mL of the resin composition was attached to a glass slide to form a resin layer. With a cover glass covering the resin layer, it was left standing at 25 °C for 24 hours. Using an optical microscope (magnification 20 times), the domain size of the resin layer after standing was measured. Regarding compatibility, a case where the domain size was less than 10 μm was evaluated as “A”, a case where the domain size was 10 μm or more and less than 20 μm was evaluated as “B”, a case where the domain size was 20 μm or more and less than 50 μm was evaluated as “C”, a case where the domain size was 50 μm or more and less than 100 μm was evaluated as “D”, and a case where the domain size was 100 μm or more was evaluated as “E”. It indicates that the smaller the domain size, the more excellent the compatibility.
[0100] [Table 2]
[0101]
[0102] [Table 3]
[0103]
Claims
1. A resin composition containing a modified styrenic elastomer with a grafting rate of maleic anhydride of 1.5 mass% or more and a thermosetting resin.
2. The resin composition according to claim 1, wherein the grafting rate is 1.5 to 10.0 mass%.
3. The resin composition according to claim 1, wherein the grafting rate is 1.8 to 10.0 mass%.
4. The resin composition according to any one of claims 1 to 3, wherein the thermosetting resin contains at least one selected from the group consisting of epoxy resins, cyanate ester resins, acrylic resins, silicone resins, phenolic resins, maleimide resins, thermosetting polyimide resins, polyurethane resins, melamine resins, and urea formaldehyde resins.
5. The resin composition according to any one of claims 1 to 3, which further contains a curing accelerator.
6. The resin composition according to any one of claims 1 to 3, wherein the content of the thermosetting resin is 10 mass parts or more with respect to 100 mass parts of the total amount of the modified styrenic elastomer and the thermosetting resin.
Citation Information
Patent Citations
Thermoplastic elastomer composition
JP2013028761A